Corridor as A Transition at Tourism Area in Yogyakarta - Hertanto, Irfan; Sunarti BD, Endang Titi; Rachmawati, Murni (IPTEK Journal of Proceedings Series, 2018)
Yogyakarta is always flooded by tourists both domestic and foreign. Malioboro street corridor, from Tugu Station to Keraton Yogyakarta, is one of the most visited tourism area in Yogyakarta. However, Ahmad Dahlan’s corridor as one of the important access that link the tourism area reduces its identity by the declining quality of its outdoor space. The analysis techniques are spatial behavior analysis, character appraisal and walkthrough analysis. The study found that declining quality of the outdoor space, such as lack of identity and sustainable street furniture that supports the activities of visitors in tourism areas. In this case, the linkage design, as a transition must be able to show the identity of the corridor to connect the surrounding area visually and spatially